Bioeconomy potential in Poland compared to EU countries - Jarosz, Zuzanna; Faber, Antoni (Polish Journal of Agronomy, 2023)
The aim of the research was to assess the potential of the bioeconomy in Poland in comparison with the European Union countries. The research used an indicator of added value, the number of people employed and the value of turnover for individual sectors included in the bioeconomy. An analysis of the structure of indicators in Poland in 2020, compared to other EU countries, allowed us to determine the level of development of the country’s bioeconomy. The analysis shows that Poland isa leader in terms of employment in the EU bioeconomy. However, the assessment of potential in terms of added value and value of turnover in the bioeconomy placed Poland in fifth position. The reason for this is Poland’s characteristic fragmented agrarian structure and excessive employment in the agricultural sector. An opportunity to redress the imbalance is to obtain EU funding and support for research and innovation.